A companion to Chinese art - Powers, Martin Joseph 1949-; Tsiang, Katherine R. (Wiley Blackwell, 2016)
"The volume offers a rich insight into China's social and political institutions, religious practices, and intellectual traditions alongside Chinese art history, theory, and criticism. It brings together an international team of scholars from East and West, whose contributions range from an overview of premodern theory, to those exploring calligraphy, fine painting, sculpture, personal accessories, and more. In addition, the companion reflects on social and cultural issues, such as the challenges of comparative history, the role of the artist in society, the contested role of gender in art production, different theories of nature that have evolved over time, and articulates the direction in which the field of Chinese art history is moving. In promoting a comparative understanding of China's long record of cultural production, this volume provides students and scholars of both Asian and non-Asian art history with an exceptional guide to the history of art in China, from its earliest incarnations to the present day." -- Provided by publisher